What Executioners Can—and Cannot—Teach Us About the Death Penalty. Issue 3 (1st September 2016) - Bandes, Susan A.
Abstract : Those who work with the condemned often come to reject the death penalty not only in individual cases, and not only on the ground that it is poorly implemented. They tend to conclude that the punishment is wrong. I argue that the perspective of the executioner helps illuminate the debate about whether to abolish capital punishment, and that indeed the perspective of those who work with the condemned raises the troubling possibility that support for the death penalty can survive only at a great remove. Jeffrie Murphy has also argued that the executioner's perspective can be useful, but I contend that Murphy asks the wrong question. His essay considers whether an executioner may, under some circumstances, take pride in his work. The better question is whether anyone ought to be asked to do such work. On this latter question, the perspective of the executioner sheds important light. Like Murphy, I draw on works by and about Albert Pierrepoint, the "last hangman" of Britain. I also draw on the perspectives of numerous executioners, wardens, chaplains, and other death row personnel. I argue that their perspectives offer a powerful argument against the main rationale for the death penalty: retribution. If retribution is keyed to the offender's character as well as his wrongful act, then post-conviction character ought to matter. The executioners' accounts share a common theme: that death row inmates change over time and hold the potential for redemption.